Ameliorating Cu2+ reduction in microbial fuel cell with Z-scheme BiFeO3 decorated on flower-like ZnO composite photocathode - Lam, S.-M. (Elsevier Ltd, 2022)
BiFeO3 nanoparticle decorated on flower-like ZnO (BiFeO3/ZnO) was fabricated through a facile hydrothermal-reflux combined method. This material was utilized as a composite photocathode for the first time in microbial fuel cell (MFC) to reduce the copper ion (Cu2+) and power generation concomitantly. The resultant BiFeO3/ZnO-based MFC displayed distinct photoelectrocatalytic activities when different weight percentages (wt) BiFeO3 were used. The 3 wt BiFeO3/ZnO MFC achieved the maximum power density of 1.301 W mâ2 in the catholyte contained 200 mg Lâ1 of Cu2+ and the power density was greatly higher than those pure ZnO and pure BiFeO3 photocathodes. Meanwhile, the MFC exhibited 90.7 removal of Cu2+ within 6 h under sunlight exposure at catholyte pH 4. The addition of BiFeO3 nanoparticles not only manifested outstanding capability in harvesting visible light, but also facilitated the formation of Z-scheme BiFeO3/ZnO heterojunction structure to induce the charge carrier transfer along with enhanced redox abilities for the cathodic reduction. The pronounced electrical output and Cu2+ reduction efficiencies can be realized through the synergistic cooperation between the bioanode and BiFeO3/ZnO photocathode in the MFC. Furthermore, the developed BiFeO3/ZnO composite presented a good stability and reusability of photoelectrocatalytic activity up to five cyclic runs. Â© 2021 Elsevier Ltd